At What Age Can Children Initiate and Execute a Mutually Beneficial Exchange? - Fong, Frankie T. K.; Kirkland, Kelly; Puah, Ee Liz; Jang, Daisung (Developmental Psychology, 2025)
Using a novel exchange paradigm, we demonstrate that Australian preschool children from middle to high socioeconomic backgrounds may be capable of executing a mutually beneficial exchange. In Study 1, 3- to 5-year-old children completed a tower building task, in which they were given an opportunity to make trading choices via preset options that could allow both them and a puppet to succeed. A majority of children across age groups selected the efficient trade option over other alternatives. In Study 2, we modified the task to have less structure. With no preset options, 5-year-old children initiated an efficient exchange to a greater extent than younger children. A different task that relied on distributing desirable versus less desirable rewards (stickers) revealed a complementary pattern. The two studies shed light on the onset and developmental trajectory of a prerequisite skill for negotiation: children's capacity to initiate and execute a mutually beneficial deal, varying across different task contexts. Public Significance Statement: Our research indicates that even 3-year-old children can trade items in a way that benefits everyone involved, provided they receive enough guidance. By the age of 5, children are able to do this with minimal help. This ability to trade resources with others is a foundational skill that leads to more advanced forms of exchange, like negotiation.